2002
DOI: 10.1093/brain/awf134
|View full text |Cite
|
Sign up to set email alerts
|

Striatal and extrastriatal dysfunction in Parkinson’s disease with dementia: a 6‐[18F]fluoro‐l‐dopa PET study

Abstract: We investigated the relative differences in dopaminergic function through the whole brain in patients with Parkinson's disease without dementia (PD) and with dementia (PDD) using 6-[18F]fluoro-L-dopa (18F-dopa) PET and a voxel-by-voxel analysis. The 10 PD and 10 PDD patients were equivalently disabled, having mean scores of 3.2 +/- 0.6 and 3.2 +/- 0.7, respectively, on the Hoehn and Yahr rating scale. 18F-dopa influx constant (Ki) images of those patients and 15 normal age-matched subjects were transformed int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(98 citation statements)
references
References 35 publications
4
92
1
1
Order By: Relevance
“…When PD patients with and without dementia were matched for age, disease duration, and disease severity, interrogation of their 18 F-dopa uptake images with statistical parametric mapping localized a reduced capacity for putamen dopamine storage in both groups. However, compared with the PD patients, the PDD patients showed additional reductions in 18 F-dopa uptake in the right caudate and bilaterally in the ventral striatum and the anterior cingulate (102). These findings support the concept that dementia in PD is associated with impaired frontal and caudate dopaminergic function.…”
Section: Dopaminergic Imagingsupporting
confidence: 68%
“…When PD patients with and without dementia were matched for age, disease duration, and disease severity, interrogation of their 18 F-dopa uptake images with statistical parametric mapping localized a reduced capacity for putamen dopamine storage in both groups. However, compared with the PD patients, the PDD patients showed additional reductions in 18 F-dopa uptake in the right caudate and bilaterally in the ventral striatum and the anterior cingulate (102). These findings support the concept that dementia in PD is associated with impaired frontal and caudate dopaminergic function.…”
Section: Dopaminergic Imagingsupporting
confidence: 68%
“…Our post mortem results generally support that conclusion. Ito and colleagues [47] reported that patients with PD and dementia had lower 18-fluoro-DOPA uptake in the ventral striatum and right caudate nucleus as compared to patients with PD only. Interestingly, we also have detected a more pronounced loss of TH in the ventral striatum in PDD group, although the difference was very small.…”
Section: Upregulation Of Arrestin and Grk Expression In Parkinson's Dmentioning
confidence: 99%
“…When PD-MCI group was directly compared with HC and PD-NC using a post-hoc test, decreased activation of ACC and SPL was demonstrated in the PD-MCI group. The abnormal engagement of ACC in PD-MCI and PD-dementia has been related to reduced dopaminergic function (Ito et al, 2002) and higher Lewy body densities (Kövari et al, 2003) and has been held responsible for poor performance of frontal executive tasks (Fera et al, 2007;Rosenberg-Katz et al, 2016).…”
Section: Discussionmentioning
confidence: 99%